PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM (Studi Kasus SMA Negeri 1 Cikarang Pusat Kabupaten Bekasi) - Enjang Sudarman (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to determine the pedagogic competencies possessed by PAI Teachers and to find out how the development of pedagogical competencies in Islamic Education Teachers in Central Cikarang 1 High School. This research uses qualitative research methods using descriptive research formats. Based on the results of the study, it is known that, the SMA 1 Cikarang Pusat High School has carried out development efforts to improve the pedagogic competencies of Islamic Education Teachers, namely through education and training, conducting scientific writing and developing independently by Islamic Religious Education Teachers. The development effort has had a positive impact on improving the pedagogical competence of Islamic Education Teachers. Based on the research conducted, it is known that qualified human resources (Teachers) are a major supporter of the success of development in Central Cikarang 1 High School.